Design of Compact Monopole Antenna using Double U-DMS Resonators for WLAN, LTE, and WiMAX Applications - Ahmed Boutejdar; Mohammad Ahmad Salamin; Saad Dosse Bennani; Soumia El Hani (Universitas Ahmad Dahlan, 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexIn this research, a novel wide-band microstrip antenna for wideband applications is proposed. The proposed antenna consists of a square radiating patch and a partial ground plane with a smal rectangular notch-shape. Two symmetrical U-slots are etched in radiating patch. The defected microstrip U-shapes and the small notch improve the antenna characterestics such impedance wideband and the gain along the transmission area. The proposed antenna is simulated on an FR4 substrate of a dielectric constant of 4.3, thickness 1.6 mm, permittivity 4.4, and loss tangent 0.018. The simulation and optimization results are carried out using CST software.The antenna topology occupies an area of 30 × 40 × 0.8 mm3 or about 0.629λg × 0.839λg × 0.017λg at 3 GHz (the centerresonance frequency). The antenna covers the range of 2.1711 to 4.0531 GHz, which meet the requirements of the wireless local area network (WLAN), worldwide interoperability for microwave access (WiMAX) and LTE (Long Term Evolution) band applications. Good VSWR, return loss and radiation pattern characteristics are obtained in the frequency band of interest. The obtained Simulation results for this antenna depict that it exhibits good radiation behavior within the transmission frequency range.